MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE ABACAGA BAGI ANAK LAMBAT BELAJAR - Nelfitri Susanti, Yosfan Azwandi, Damri (Jurnal Penelitian Pendidikan Khusus, 2013)
The research find the problems of a slow learning child the difficulty in reading the beginning. Based on assessment children still have difficulties in combining some consonants (b, d, g, p, q, r) into syllables and words. Researchers using the method abacaga. The baseline with percentage of 10%-17% and  intervention percentage to 50%-100%. Thus, the hypothesis in  acceptable. Abacaga method can improve the child's ability to read the beginning of a slow learning.